Clinical Importance of Foramen Magnum Measurements for Determining Sex - CT Scan Based Study using Discriminant Function Analysis - Bhoi , S; Das , S; Subramania , D B; Mishra , A; Ganapathy , S; Ravi , K (Journal of Indian Academy of Forensic Medicine, 2023)
Identification of an individual is one of the important objectives of an autopsy. In forensic practice, partial identification from the bones in the form of sex is possible from the bones or any part of it. Foramen magnum (FM) measurements from skull or Computer Tomography (CT) scan images are useful for determining sex in different populations. The present study was undertaken with an objective to assess the clinical importance of FM measurements for determining sex from CTscan images in a south Indian population. The parameters studied were the length and breadth of foramen magnum, foramen magnum index (FMI) and area of foramen magnum (AFM). The sample size was 384 consisting of 245 males and 139 females of south Indian origin. Independent student t-test showed that all the studied parameters except FMI was significantly different between the two sexes. Discriminant function analysis was used to differentiate sex from the measured parameters by using the split data method. Foramen magnum length (FML) was the best sex differentiating predictor with an accuracy of 70.9%. When all the parameters were taken together the accuracy increased marginally to 71.5%. FM measurements can be used to determine sex from CTscan measurements in a south Indian population but it is better to use it as an adjunct to other methods to increase the precision.